2010
DOI: 10.3233/jad-2010-100159
|View full text |Cite
|
Sign up to set email alerts
|

Familial Alzheimer's Disease Mutations in Presenilins: Effects on Endoplasmic Reticulum Calcium Homeostasis and Correlation with Clinical Phenotypes

Abstract: Mutations in presenilins (PS1 and PS2) are responsible for approximately 40% of all early onset familial Alzheimer’s disease (FAD) monogenic cases. Presenilins (PSs) function as the catalytic subunit of γ-secretase and support cleavage of the amyloid precursor protein (APP). We previously discovered that PSs also function as passive endoplasmic reticulum (ER) calcium (Ca2+) leak channels and that most FAD mutations in PSs affected their ER Ca2+ leak function. To further validate the relevance of our findings t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 46 publications
6
69
0
2
Order By: Relevance
“…Our results indicate that altered Ca 2+ homeostasis in the cerebella of these patients might be yet another consequence, which does not necessarily depend on Aβ-or pTau-related processes. Finally, our data are in line with a study in which FAD-derived lymphoblasts showed altered ER Ca 2+ homeostasis (34). However, in this lymphoblast study, PS1 E280G mutation showed preserved ER Ca 2+ leak function.…”
Section: Figuresupporting
confidence: 76%
“…Our results indicate that altered Ca 2+ homeostasis in the cerebella of these patients might be yet another consequence, which does not necessarily depend on Aβ-or pTau-related processes. Finally, our data are in line with a study in which FAD-derived lymphoblasts showed altered ER Ca 2+ homeostasis (34). However, in this lymphoblast study, PS1 E280G mutation showed preserved ER Ca 2+ leak function.…”
Section: Figuresupporting
confidence: 76%
“…Subsequent reports employed D1-ER measurements in transfected primary hippocampal neurons from triple transgenic mice (harboring the PS1M146V-KIN mutation), but only a qualitative description was provided without quantitative analyses of leak rates (30). The use of the AI as an indirect estimate of [Ca 2ϩ ] ER to infer conclusions regarding the role of PS in ER Ca 2ϩ permeability has been the basis of the primary quantitative analysis in the previous studies (26,28,30,31). When we measured the AI, we observed the phenomenon reported in these studies; PS DKO and hPS1M146L expressing fibroblasts had an enhanced area under their whole cell ionomycin-induced Ca 2ϩ release versus time curve compared with WT hPS1-and hPS1D257A-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, this indirect measurement is compromised by strong influences of Ca 2ϩ clearance and buffering. Mag-Fura 2 was measured in permeabilized PS DKO and WT MEF cells (31) and in PS DKO transiently and stably expressing FAD mutants (26,27) to quantify [Ca 2ϩ ] ER . However, Mag-Fura 2 may compartmentalize into many distinct intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…We found that many FAD mutations in PS1 disrupt this Ca 2+ leak function [56][57][58], resulting in overloaded ER Ca 2+ stores and exaggerated ER Ca 2+ release in double PS knock-out fibroblasts [56][57][58], cultured hippocampal neurons from PS double-knockout mice and PS1-M146V mutant neurons [51] and lymphoblasts from FAD patients [58]. These observations suggest that PS1 plays a pivotal role in deranged Ca 2+ in AD and they also provide further support for the contribution of PS1 to Ca 2+ homeostasis in neurons.…”
Section: Presenilins Are Er Ca 2+ Leak Channelsmentioning
confidence: 99%
“…Could this variant AD somehow be explained by the altered ER Ca 2+ signaling caused by PS1-FAD mutations? Over a series of experiments [56][57][58], we have tested a total of 23 FAD mutations in PS1, 1 FAD mutation in PS2 and 3 FTD implicated PS1 mutations. We concluded that 14 FAD mutations abolished ER Ca 2+ leak function of PS ( Figure 2A).…”
Section: Er Ca 2+ Leak and Variant Admentioning
confidence: 99%